A Comprehensive Review of Coptidis Rhizoma and Magnoliae Officinalis Cortex Drug Pair and Their Chemical Composition, Pharmacological Effects and Pharmacokinetics Analysis - Xie Q; Chen J; Yang H; Liang J; Ma R; Guo J; Zeng X (Dove Medical Press, 2024)
Qian Xie, Jiarou Chen, Hongyan Yang, Jianlong Liang, Rong Ma, Jialiang Guo, Xuxin Zeng School of Medicine, Foshan University, Foshan, 528000, People's Republic of ChinaCorrespondence: Rong Ma; Xuxin Zeng, School of Medicine, Foshan University, Foshan, 528000, People's Republic of China, Email 648510213@qq.com; adhesion2002@163.comAbstract: Herbal pairs are unique combinations of two relatively fixed herbs that are used in clinical practice. This is the most fundamental and straightforward form of multiple herbal treatment that aims to attain specific efficacy through unique methods. Coptidis Rhizoma ("Huanglian" in Chinese) and Magnoliae Officinalis Cortex ("Houpo" in Chinese) which are commonly used in combination and could also be used as important components of other prescriptions to treat damp-heat dysentery, splenic and stomach disorders, and qi stagnation in clinical practice. However, there is currently no summary on the compatibility of Huanglian and Houpo about traditional use, phytochemistry, and pharmacological activity. It was found the combination or separate extraction of the two drugs may affect the main active components, and new components may be produced after the combined extraction. At the same time, Huanglian and Houpo herb pair exhibited antiviral, anti-inflammatory, antibacterial and other pharmacological effects. At present, research mainly focuses on the indicator components of Huanglian and Houpo, such as berberine, magnolol, and magnolol. The models used for pharmacological validation are limited, mainly including ulcerative colitis, pneumonia, bacterial infections, etc. In order to verify the pharmacological activity of the combination of Huanglian and Houpo, it is necessary to try more in vitro and in vivo models. It's still need to study the compatibility mechanism of the Huanglian and Houpo drug pair, including but not limited to the interactions between different components and the impact of compatibility on efficacy, bioequivalence studies, and the impact of different dosage forms on pharmacokinetics in the future. It's believed that the systematic review provided comprehensive information for the study of Huanglian-Houpo drug pair, which will help highlight the importance of the Huanglian-Houpo herb pair and provide some clues for future research on this herb pair.Keywords: Coptidis Rhizoma, Magnoliae Officinalis Cortex, drug pair, chemical constituents, pharmacological effects